Ezofagealni, gastrični, kolorektalni, pankreatični, hepatocelularni karcinomi i holangiokarcinomi u Severnoj Makedoniji: serija pacijenata lečenih na Univerzitetskoj klinici, između 2015. i 2019. godine - Grivcheva Stardelova, Kalina (Srpski medicinski časopis Lekarske komore, 2021)
Introduction/Aim: The global cancer burden tends to increase. Tumours originating from the gastrointestinal (GI) tract such as stomach, colon and liver are among the five most common cancers in both men and women worldwide. The incidence of GI cancers shows significant geographical variation, with colorectal cancer incidence higher in Western Europe and North America, and gastric and liver cancer incidence higher in Asia and Africa. The incidence and mortality rate in North Macedonia is similar to those of Western European countries.Material and methods: The paper provides an overview of cases at the University Clinic for Gastroenterohepatology in Skopje over a five-year period (2015-2019), analysed by age, gender and cancer site.Results: A total of 1484 patients with colorectal cancer were detected, followed by763 patients with gastric cancer and 88 patients with esophageal cancer. Most patients were in age group 60-69, with exception to esophageal cancer. In addition, hepatocellular carcinoma was diagnosed in 48 patients, cholangiocarcinoma in 34 patients and carcinoma of extrahepatic bile duct in 59 patients. In 355 patients nonspecific malignancy of liver was diagnosed. Increasing incidence of pancreaticcarcinoma was observed, with 528 patients (287 male and 241 female) diagnosed, mostly in age groups 60-69 and 70-79 years.Conclusions: Gastrointestinal cancers in North Macedonia, show increasing trend, especially in men with a predominance of colorectal, pancreatic and liver cancer. To decrease incidence of these diseases, it is important to ensure access and availability to therapy for B and C hepatitisand to update the colorectal cancer screening program.
Keywords: gastrointestinal carcinoma; gastric cancer; pancreatic cancer; hepatocellular cancer; esophageal cancer; colorectal cancer